The single European market, Swedish investment liberalisation, and horizontal and vertical multinationals - Thomas Mathä (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
This paper analyses the effects of the Single European Market and Swedish Investment liberalisation on the structure of Swedish multinationals with their EU affiliates. The empirical results suggest that the determinants associated with horizontal and vertical multinationals have become increasingly relevant between 1974 and 1994. Horizontal multinationals are increasingly deterred by large plant-level economies of scale, increasingly associated with large trade costs and relative factor endowment similarities, while vertical multinationals are increasingly associated with relative factor endowment differences. This suggests that European integration has increased competitive pressures to enhance efficiency in exploiting economies of scale, and specialisation according to comparative advantages.
Keywords: F12; F21; F23; 330; Single European Market; Swedish Investment Liberalisation; Country Size; Factor Endowments; Horizontal & Vertical Multinationals; EU-Binnenmarkt; Außenhandelsliberalisierung; Multinationales Unternehmen; Horizontale Konzentration; Vertikale Konzentration; Schweden; Makroökonomischer Einfluss